Peranan Pola Konsumsi dan Gaya Hidup terhadap Prevalensi Diabetes Tipe 2 di Indonesia - Anita Roserlina; Nurheni Sri Palupi; Endang Prangdimurti (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2015)
Type 2 diabetes is a metabolic disease associated with lifestyle, including consumption behaviors. This study was conducted to examine the relationship between behaviors of consumption and lifestyle on prevalence of type 2 diabetes in Indonesia. The risk factor determined by univariate analysis. Relation between diabetes prevalence risk factors analyzed using bivariate methods. To determine main risk factors of diabetes used multivariate analysis. Scoring models developing to predict type 2 diabetes risk based on sensitivity and specificity test from major risk factors, to obtain cut off point score for respondents who predicted have diabetes risk. Analysis showed that factor of sweet beverages consumption has OR value (odds ratio) 1.25. This value means that respondents who frequently consume sweetened foods and drinks will be at diabetes risk 1.25 times, compared from not consume. Risk value of consumption food made from flour is 1.22. Diabetes risk for respondents who have moderate physical activity is 1.15 times and strenuous physical activity is 1.26 times. Diabetes risk for not consume fruits and vegetables is 1.12 times and 1.2 times from respondents who consumed. Calculations models predicted risk of type 2 diabetes determined based on the value of the score (cut-off point) ≥20.